2015
DOI: 10.1556/1886.2015.00021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bloodstream Infections during Chemotherapy-Induced Febrile Neutropenia in Patients with Malignant Hematological Diseases: Single Center Experience

Abstract: From year to year, it is important to get an overview of the occurrence of causative agents in febrile neutropenic patients to determine the empiric treatment. Thus our aims were to evaluate a four-year period regarding the prevalence of bloodstream infections and the most important causative agents. During this period, 1,361 patients were treated in our hematology ward because of various hematological disorders. 812 febrile episodes were recorded in 469 patients. At that time, 3,714 blood culture (BC) bottles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 19 publications
1
23
0
4
Order By: Relevance
“…Regarding causes of fever, it is noteworthy that 42.5% of all febrile episodes were of unknown origin, a concept modified by Engelhart et al that means "fever without evidence of a specific infection at any site, without isolation of a specific microorganism from body specimens or without any apparent non-infectious cause" [6]. This number is comparable with the findings of Burutaran et al, who found a prevalence of 38% of fever or unknown origin [9], and with a prevalence of 53% described by Piukovics et al [10]. Studies suggest that at least half of all neutropenic patients with fever of unknown origin have an occult infection, underlining the relevance of this entity [6].…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…Regarding causes of fever, it is noteworthy that 42.5% of all febrile episodes were of unknown origin, a concept modified by Engelhart et al that means "fever without evidence of a specific infection at any site, without isolation of a specific microorganism from body specimens or without any apparent non-infectious cause" [6]. This number is comparable with the findings of Burutaran et al, who found a prevalence of 38% of fever or unknown origin [9], and with a prevalence of 53% described by Piukovics et al [10]. Studies suggest that at least half of all neutropenic patients with fever of unknown origin have an occult infection, underlining the relevance of this entity [6].…”
Section: Discussionsupporting
confidence: 72%
“…Our study shows that almost 35% of all hospitalizations in a hematology-oncology clinic of a portuguese oncology hospital were complicated by fever. Hungarian hospital [10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations